Assessment Tools for Measuring Meaning in Life - Nilchantuk, Chureerat (Ratchaphruek Journal, 2020)
This article aimed to study the assessment tools related to the meaning of life. The meaning of life illustrates how a person lives with the meaningful life, and it is unique. There are correlations between the meaning of life and several positive psychological variables, for instance, adaptability, and resilience. The research articles and academic references in this study have been retrieved from the electronic files which available in Chulalongkorn University Library’s database, while the searching keywords paper are ‘Assessment, meaning in life’ and ‘Measurement, meaning of life.’ The study illustrates 7 meaning of life assessment tools, however, only 4 have been translated and used in Thailand, namely, The Purpose in Life-Part A: PIL-Part A, The Seeking of Noetic Goals: SONG, The Meaning in Suffering Test-Part 1: MIST-Part1, and The Meaning in Life Questionnaire: MLQ. These 4 instruments adopted the perspective of logotherapy and applied research methodology in the development process. These 4 instruments have a proper psychometric property which can be used to assess the meaning of life, and for further development.